Which Pluricentrism? Tensions and Conflicts on the Construction of the Spanish and Portuguese International Linguistic Space. Issue 1 (2nd January 2021) - Lagares, Xoán Carlos
Abstract : Pluricentrism presupposes the existence of several territories under the influence of different linguistic usage norms. From a glottopolitical perspective, focused on the conflicts and tensions involved in the control and understanding of the language as a social object, the normative dynamics of Spanish and Portuguese are compared, paying attention to the differences in the colonizing processes undertaken by Spain and Portugal and the ways in which the international spaces of both languages were constituted. According to its specific characteristics, the international space of Spanish has been defined in this work as a "mixed pluricentrism" and that of Portuguese as an "unequal bicentrism." The differences in the constitution of linguistic markets in both languages allow us to understand their conflicting social representations, such as "united" or "divided" languages, as well as political and ideological initiatives to build a notion of an international language. The political tensions over the establishment of the standard norm also depend on the differences in the participation of normative agents, linked to academies of the language in the case of Spanish, but not in the case of Portuguese, and to the establishment of diverse negotiating forums.